Pelatihan Gerak Dasar Pada Olahraga Tradisional di SD Negeri Binaan Khusus Dumai Timur - Apriani, Leni; Fatmawati, Fatmawati; Alpen, Joni; Ardisty, Aryuni Khiran; Hudah, Maftukin; Maliki, Osa; Pradipta, Galih Dwi (Jurnal Pengabdian Olahraga Masyarakat, 2023)
Â This study aims to have its own uniqueness and cultural elements. For a society, traditional games can affect a person's self-development because it includes the development of the soul, nature and culture of the social life of young people in the future in order to describe how the use of traditional games in developing gross motor skills in early childhood is efficient or not when used in learn how to teach. This service activity was carried out at the Special Guidance Elementary School in East Dumai. The development of gross motor skills should be in line with the rules put forward by experts. Likewise with the hulahop game which makes students develop their gross motor skills because the game is in accordance with the gross motor rules that should exist in children. The use of Hulahop games to develop children's gross motor skills is very efficient and suitable for use in developing these aspects.ABSTRAKPengabdian ini bertujuan mempunyai keunikan dan unsur kebudayaan yang tersendiri. Bagi sesebuah masyarakat, permainan tradisional dapat mempengaruhi perkembangan diri seseorang kerana ia meliputi perkembangan jiwa, sifat dan kebudayaan hidup sosial anak muda pada masa akan datang guna mendeskripsikan bagaimanakah penggunaan permainan tradisional dalam mengembangkan kemampuan motorik kasar anak usia dini, apakah efisien atau tidak bila digunakan dalam belajar mengajar. Kegiatan Pengabdian ini dilakukan di SD Negeri Binaan Khusus Dumai Timur. Â Pengembangan kemampuan motorik kasar hendaknya sejalan dengan kaidah yang dikemukakan para ahli. Begitu pula dengan permainan hulahop yang membuat peserta didik berkembang kemampuan motorik kasarnya dikarenakan permainannya yang sesuai dengan kaidah-kaidah motorik kasar yang seharusnya ada pada diri anakpenggunaan permainan Hulahop guna mengembangkan kemampuan motorik kasar anak sangatlah efisien dan cocok digunakan dalam menggembangkan aspek tersebut.